“Be a breeze. a cool cool breeze”. The air and wind as mediums of black non/being and love in Toni Morrison’s Song of Solomon - Mózes, Dorottya (Studia Anglica Posnaniensia, 2023)
Even though the critical commentary on Song of Solomon focuses on the motif of Black flight and the protagonist Milkman’s quest for identity, the specific questions and problems raised by the motifs of air and wind have not been attended to. Therefore, this paper conducts close readings of airy and windy scenes that blow up, flow, and float in Song. If air and atmosphere signify the totality of the antiblack climate, forced aerial movement in Song symbolizes how individual and collective lives are moved, uprooted, and swept up in Middle Passage, racial slavery, and its afterlives. However, the paper also shows how airborne affects, ecologies, and motion – including gingery air, cool breezes, strong winds, or airy flights – disrupt the antiblack atmosphere by creating microclimates of connection, joy, and queer potentiality.